Evaluasi terhadap Peran Satuan Polisi Pamong Praja dalam Perlindungan Hak Asasi Manusia bagi Masyarakat - Oki Wahju Budijanto (Badan Strategi Kebijakan Hukum, 2012)
The evaluation over the role of Civil Service Police Unit in terms of human rights protection for people aims to determine the level of understanding of members of municipal police regading the values of human rights related to their duties, and the implementation of Article 8 of the Governmental Regulation No. 6 Year 2010 on Civil Service Police Unit, as well as the implementation of guidance and oversight functions of the Regional Government over the municipal police. The result of evaluation carried out is expected to be materials to enrich scientific literatures and the literature on human rights field. Aside from that, it be used as a material in making the formulation of policy recommendations related to the improvement of municipal police duties in the field.The evaluation was conducted from February to September 2011. Location of this evaluation covers four provinces, namely Southeast Sulawesi (Kendari), Lombok (Mataram City), South Kalimantan (Banjarmasin) and East Java (Surabaya). The method used is qualitative and quantitative approach. While data collection techniques used in this evaluation comprise in-depth interviews, questionnaires, and tests, as well as documentary study of secondary data. Furthermore, the data obtained in the tabulation were then to be processed, and the conclusions drawn derives from some interpretations of the findings in the field.The results of the evaluation of the municipal police who are in Southeast Sulawesi, West Nusa Tenggara, South Kalimantan and East Java overall have a lack understanding of human rights, so there have been many people encountered violence committed by the officers in carrying out daily tasks. Some numerous clashes often occurred in places such as the demolition, is being done to Merchants Street Markets (PKL), the demonstrators, and bums or beggars. Guidance and supervision to the municipal police conducted so far is still considered not effective.Based on the evaluation results, it can be concluded that, (1) the understanding of the majority of members of municipal police is still considerably lacking, (2) the implementation of the provisions of Article 8 of the Governmental Regulation No. 6 of 2010 on municipal police stating